2014
DOI: 10.1021/ie500109r
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Kinetic Study on the Influence of Iron Oxide on the Selective Noncatalytic Reduction DeNOx Process

Abstract: The influence of Fe 2 O 3 on the SNCR deNO x process was investigated in a fixed-bed reactor. The experimental results demonstrated that Fe 2 O 3 has an inhibitory effect on the SNCR deNO x process that is more notable at low temperatures. Interactions between Fe 2 O 3 and NH 3 , Fe 2 O 3 -catalyzed NH 3 oxidation, and NO reduction by NH 3 were studied experimentally. In the absence of O 2 , Fe 2 O 3 was reduced by NH 3 to form Fe, which then catalyzed NH 3 decomposition to N 2 and H 2 . Fe 2 O 3 also catalyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Tests were carried out to investigate its effects on the characteristics of NO removal over circulating ash (series 1 in Table ). The tendencies of NO concentrations in NH 3 -SNCR with circulating ash are provided in Figure a, and the previous results over iron oxide and CaO are also listed for comparison. It was found that the changes of NO concentrations over circulating ash obtained in the present study were similar to those over iron oxide and CaO particles reported in previous studies, which indicated that the circulating ash exhibited significant catalytic effects on NO removal in the NH 3 -SNCR process.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Tests were carried out to investigate its effects on the characteristics of NO removal over circulating ash (series 1 in Table ). The tendencies of NO concentrations in NH 3 -SNCR with circulating ash are provided in Figure a, and the previous results over iron oxide and CaO are also listed for comparison. It was found that the changes of NO concentrations over circulating ash obtained in the present study were similar to those over iron oxide and CaO particles reported in previous studies, which indicated that the circulating ash exhibited significant catalytic effects on NO removal in the NH 3 -SNCR process.…”
Section: Resultsmentioning
confidence: 98%
“…Then, these precursors could dissociate to NO in the gas phase as eq , resulting in the catalytic oxidation of NH 3 over circulating ash. Besides, part of the NH 2 adsorbed species could also react with the gaseous or adsorbed NO species, as eq to eq , leading to the reduction of NO especially at high temperatures. According to the results in the present study, compared with the homogeneous gas-phase reactions, the presence of circulating ash could dominantly enhance the catalytic oxidation of NH 3 adsorbed species (NH 2 intermediates) to generate the precursors of NO, resulting in the suppression of NO reduction in the NH 3 -SNCR process. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2−4 A number of processes for the removal of nitrogen oxides (NO x ) emitted from stationary combustion facilities have been developed, such as selective catalytic reduction (SCR) and selective noncatalytic reduction (SNCR). 5,6 However, SCR requires expensive catalysts, SNCR requires high temperatures, (i.e., increased process costs). In addition to the dry denitrification above, there are also wet denitrification such as oxidation denitrification 7 and complexation reduction denitration.…”
Section: Introductionmentioning
confidence: 99%
“…The nitrogen oxides (NO x ) are mainly produced by industrial production and vehicle exhaust. , NO x and its secondary pollutants induced by NO x such as photochemical smog, acid rain, ozone hole, and PM 2.5 , are harmful to the human health. A number of processes for the removal of nitrogen oxides (NO x ) emitted from stationary combustion facilities have been developed, such as selective catalytic reduction (SCR) and selective noncatalytic reduction (SNCR). , However, SCR requires expensive catalysts, SNCR requires high temperatures, (i.e., increased process costs). In addition to the dry denitrification above, there are also wet denitrification such as oxidation denitrification and complexation reduction denitration. , And all of these processes require the continuous addition of oxidizing agents or reducing agents to maintain the denitrification efficiency.…”
Section: Introductionmentioning
confidence: 99%